ANALISIS PENGARUH ATMOSFER TOKO, PRICE DISCOUNT DAN SALES PERSON TERHADAP IMPULSE BUYING MELALUI EMOTIONAL RESPONSE (Studi Pada Konsumen Hypermarket Kota Semarang) - Hidayat, Yahya Nuur; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2017)
The development of retail business in Semarang has increasing, ranging from minimarkets, supermarket, to the hypermarket. It can not be separated from the demands of people who want a very practical, comfortable, and saving time. This lead tight competition to the retail business. Consumers who feel comfortable with the store atmosphere and then coupled with the emotional motivation allow impulse purchases will increase. This research is motivated by intense competition in the modern retail industry in Semarang. That is because a lot of new faces emerging modern retail players. However, there is one thing on consumer purchasing behavior in modern retailing that steal the show. This research used five variables such as store atmosphere, price discounts, sales person, emotional response, and impulse buying. The hypothesis testing used 100 respondents as the data. The object of this research is that consumers at Hypermarket Semarang. Technique of analysis is used software program of Statistical Package fo Social Science (SPSS) 20.The results showed that: (1) Store atmosphere positive and significant impact on emotional response. (2) Price discount positive and significant impact on emotional response. (3) Sales person positive and significant impact on the emotional response. (4) Emotional response positive and significant impact on the impulse buying.